Khalifa University Reachback Program Supporting Prevention of Illicit Nuclear and Radiological Material Smuggling in the United Arab Emirates - Braden Goddard; Alexander A Solodov; Patrick J Simmons (International Journal of Nuclear Security, 2016)
Trafficking of Illicit nuclear or radiological materials is a global threat which can involve and adversely affect any country. Ultimately, it is the responsibility of each state to prevent and combat illicit nuclear trafficking by screening all cargo and travelers entering, exiting, and transiting through its borders. As a part of the national radiation detection infrastructure of the United Arab Emirates (UAE), a reachback program was established at Khalifa University (KU) to provide capabilities for adjudication of radiation alarms at Khalifa Port and other radiation portal monitor (RPM) locations. In addition to the main mission, KU Reachback aims to educate and prepare local talent to lead these vital efforts in the future. This is particularly important because the UAE, similar to other newcomers to the nuclear industry, faces human capital challenges which can be addressed using domestic or regional solutions.
Keywords: Reachback; Radiation Portal Monitors; Nuclear Security